Characteristics and genesis of dolomite in the lower Cambrian Xiaoerbulake Formation of the western Tarim Basin, China - Zhou, Hui; Gao, Da; Huang, Lili; Zhu, Guangyou; Zhang, Tianfu; Liu, Jingjiang; Zhai, Xiufen; Xiong, Ran; Wang, Shan; Zhang, Yuanyin (Frontiers in Earth Science, 2023)
The Lower Cambrian Xiaoerbulake Formation consist of thick dolostones which are high-quality hydrocarbon reservoir in the western Tarim Basin, but the origin of dolomite is still controversial, which lead to poor understanding to the origin of reservoir beds. By using the latest core data of Well XKD-1, we analyzed the petrology and geochemistry of the formation in order to clarify the genesis of dolomite. The geochemical analysis includes Sr, C, and O isotopes, and in-situ minor element and rare Earth element measurements for different types of dolomites by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Four types of lithofacies are recognized in the Xiaoerbulake Formation based on different textures, which are laminated dolostone, thrombolite dolostone, bacteria-bonded dolostone, and grain dolostone. Two types of dolomites can be separated which are matrix dolomite (MD) and cement dolomite (CD). MD is the primary type of laminated and bacteria-bonded dolostone, and CD was developed mainly in grain dolostone and thrombolite dolostone. The δ13C and δ18O indicate that the grain dolostone and thrombolite dolostone have undergone more intensive diagenetic modification. On the contrary, the diagenetic modification of laminated and bacteria-bonded dolostone are relatively weak, which implies that the dolomitization of the latter two lithofacies occurs before burial stage. The 87Sr/86Sr ratio indicates that the corresponding fluid for dolomitization was seawater or marine-origin fluids. The MD was formed in the near-surface stage via the penecontemporaneous dolomitization of seawater or hyper-saline seawater. The dolomitization of CD occurred in the burial environment with the porosity was filled by marine-origin fluid, indicating a seepage-reflux dolomitization process. Both types of dolomites are partially affected by hydrothermal activities.